2010
DOI: 10.1002/jbmr.114
|View full text |Cite
|
Sign up to set email alerts
|

NVP-BEZ235, a dual pan class I PI3 kinase and mTOR inhibitor, promotes osteogenic differentiation in human mesenchymal stromal cells

Abstract: Osteoblasts are bone-forming cells derived from mesenchymal stromal cells (MSCs) that reside within the bone marrow. In response to a variety of factors, MSCs proliferate and differentiate into mature, functional osteoblasts. Several studies have shown previously that suppression of the PI3K and mTOR signaling pathways in these cells strongly promotes osteogenic differentiation, which suggests that inhibitors of these pathways may be useful as anabolic bone agents. In this study we examined the effect of BEZ23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 69 publications
3
42
0
Order By: Relevance
“…However, we failed to detect activation of these pathways in response to PDGF in bone marrow-derived MSCs (data not shown), which may be due to cell-type differences or the PDGF isoform used. In hMSCs, PDGF strongly activates the PI3 kinase pathway and previous studies have suggested that the anti-differentiative effects of PDGF could be inhibited using PI3 kinase inhibitors such as Wortmannin and LY94002 (Kratchmarova et al 2005, Fitter et al 2008, Martin et al 2010. Consistent with this view, we have demonstrated that imatinib is a potent inhibitor of PDGF-induced Akt phosphorylation, a major substrate of the PI3 kinase pathway.…”
Section: Imatinib Promotes Adipogenesis S Fitter and Others 235supporting
confidence: 89%
See 1 more Smart Citation
“…However, we failed to detect activation of these pathways in response to PDGF in bone marrow-derived MSCs (data not shown), which may be due to cell-type differences or the PDGF isoform used. In hMSCs, PDGF strongly activates the PI3 kinase pathway and previous studies have suggested that the anti-differentiative effects of PDGF could be inhibited using PI3 kinase inhibitors such as Wortmannin and LY94002 (Kratchmarova et al 2005, Fitter et al 2008, Martin et al 2010. Consistent with this view, we have demonstrated that imatinib is a potent inhibitor of PDGF-induced Akt phosphorylation, a major substrate of the PI3 kinase pathway.…”
Section: Imatinib Promotes Adipogenesis S Fitter and Others 235supporting
confidence: 89%
“…Suppression of PI3 kinase using pharmacological inhibitors has been shown to promote MSC differentiation (Kratchmarova et al 2005, Fitter et al 2008, Martin et al 2010, suggesting that this pathway is important for transducing the inhibitory effects of PDGF on MSC differentiation. Consistent with this hypothesis, imatinib is a potent inhibitor of PDGF-induced PI3 kinase activation, as evidenced by a dose-dependent decrease in the phosphorylation of Akt (Fig.…”
Section: Inhibition Of P110a Promotes Adipogenesis and Adiponectin Sementioning
confidence: 99%
“…Normally, FBN1 is abundant in the connective tissue of the aorta, ligature of the human eye lens, bones, and lungs. Lee et al, 2010b;Martin et al, 2010) osteogenesis, depending on cell type or differentiation stages. Recently, it has been reported that bone matrix secretes IGF-1 (insulin-like growth factor-1) to recruit normal BMMSCs for bone remodeling by activating mTOR signaling (Xian et al, 2012), indicating that mTOR may contribute to the activation of different sets of biological regulatory controls under certain conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13] MM is frequently associated with dysregulation and/or mutations of signaling genes such as RAS, PTEN, FGF, c-Myc, and CDKN pathways. [6][7][8][9][10][11][12][13] These pathways often signal via TORC1/2 to regulate protein translation and cytoskeletal dynamics that are collectively required for cell division, growth, motility, and survival. [6][7][8][9][10][11][12][13] Recent reports have shown that Deptor is an mTORinteracting protein that is highly overexpressed in MM with cyclin D1/D3 (t:11;14 and t:6;14) or c-MAF/MAFB translocations (t: 14; 16), which are present in 30% of MM patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although no mutations are present in PI3K/AKT genes, this pathway is activated in the majority of patients with MM through either external signaling from insulin growth factor 1 (IGF-1), receptor tyrosine kinases (RTKs), or other dysregulations, including genetic mutations in other pathways or epigenetics that lead to activation of this pathway. [5][6][7][8][9][10][11][12][13] MM is frequently associated with dysregulation and/or mutations of signaling genes such as RAS, PTEN, FGF, c-Myc, and CDKN pathways. [6][7][8][9][10][11][12][13] These pathways often signal via TORC1/2 to regulate protein translation and cytoskeletal dynamics that are collectively required for cell division, growth, motility, and survival.…”
Section: Introductionmentioning
confidence: 99%